Effects of the anti-RANKL antibody denosumab on joint structural damage in patients with rheumatoid arthritis treated with conventional synthetic disease-modifying antirheumatic drugs (DESIRABLE study): a randomised, double-blind, placebo-controlled phase 3 trial. Issue 7 (29th April 2019) - Takeuchi, Tsutomu; Tanaka, Yoshiya; Soen, Satoshi; Yamanaka, Hisashi; Yoneda, Toshiyuki; Tanaka, Sakae; Nitta, Takaya; Okubo, Naoki; Genant, Harry K; van der Heijde, Désirée
Abstract : Objective: To evaluate the efficacy of denosumab in suppressing joint destruction when added to conventional synthetic disease-modifying antirheumatic drug (csDMARD) therapy in patients with rheumatoid arthritis (RA). Methods: This was a multi-centre, randomised, double-blind, parallel-group, placebo-controlled phase 3 study in Japan. Patients with RA aged ≥20 years receiving csDMARDs were randomly assigned (1:1:1) to denosumab 60 mg every 3 months (Q3M), denosumab 60 mg every 6 months (Q6M) or placebo. The change in the modified total Sharp score (mTSS) and effect on bone mineral density (BMD) at 12 months was evaluated. Results: In total, 654 patients received the trial drugs. Denosumab groups showed significantly less progression of joint destruction. The mean changes in the mTSS at 12 months were 1.49 (95% CI 0.99 to 1.99) in the placebo group, 0.99 (95% CI 0.49 to 1.49) in the Q6M group (p=0.0235) and 0.72 (95% CI 0.41 to 1.03) in the Q3M group (p=0.0055). The mean changes in bone erosion score were 0.98 (95% CI 0.65 to 1.31) in the placebo group, 0.51 (95% CI 0.22 to 0.80) in the Q6M group (p=0.0104) and 0.22 (95% CI 0.09 to 0.34) in the Q3M group (p=0.0001). No significant between-group difference was observed in the joint space narrowing score. The per cent change in lumbar spine (L1–L4) BMD in the placebo, Q6M and Q3M groups were −1.03%, 3.99% (p<0.0001) and 4.88% (p<0.0001). No major differences were observed among safety profiles. Conclusions: Denosumab inhibits the progression of joint destruction, increases BMD and is well tolerated in patients with RA taking csDMARD.